2022
DOI: 10.1017/s0021932021000651
|View full text |Cite
|
Sign up to set email alerts
|

Safer sex negotiation and parity among women in sub-Saharan Africa

Abstract: Women’s ability to negotiate for safer sex has effects on their sexual and reproductive health. This study investigated the association between safer sex negotiation and parity among women in sub-Saharan Africa. The data were sourced from the Demographic and Health Surveys of 28 sub-Saharan African countries conducted from 2010 to 2019. A total of 215,397 women aged 15–49 were included in the study. Multilevel logistic analysis was conducted to examine the association between safer sex negotiation and parity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
(47 reference statements)
1
5
0
Order By: Relevance
“…Four, the determinants of women's ability to negotiate safer sex differ among contraceptive users and non-users. In line with existing studies, it was found among nonusers that child marriage [44], mass media [1], healthcare autonomy [50], financial autonomy [51], parity [45], household wealth, and partners' education [4] are important determinants of safer sex negotiation. However, most of these determinants were not found significant among contraceptive users.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…Four, the determinants of women's ability to negotiate safer sex differ among contraceptive users and non-users. In line with existing studies, it was found among nonusers that child marriage [44], mass media [1], healthcare autonomy [50], financial autonomy [51], parity [45], household wealth, and partners' education [4] are important determinants of safer sex negotiation. However, most of these determinants were not found significant among contraceptive users.…”
Section: Discussionsupporting
confidence: 70%
“…The threshold of women's autonomy is the ability to negotiate safer sex with partners. Such negotiation in many developing countries where patriarchy remained dominant is likely to lead to a positive change in existing gender norms within marital or sexual relationships, which may translate into improving women's capacity to protect themselves from sexually transmitted infections [22,25], unintended pregnancies [23], and other adverse health outcomes [26,27]. In this paper, we assessed the prevalence of women's ability to negotiate safer sex by contraceptive status, and also examined the determinants of women's ability to negotiate safer sex among contraceptive users and non-users.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is essential to recognise that the impact of religion on contraceptive use is influenced by a complex interplay of socioeconomic and cultural factors 28 42. Factors such as education and gender equality not only affect women’s access to and utilisation of modern contraceptives but also their ability to properly use traditional contraceptives, which require knowledge of the ovulatory cycle and negotiation within intimate relationships 12–14 43 44…”
Section: Discussionmentioning
confidence: 99%